THEORETICAL FOUNDATIONS FORMING THE CREATIVE COMPETENCE OF STUDENTS IN THE PROCESS OF TEACHING - Inessa Vyacheslavovna Morkhova , Svetlana Khamidovna Koneva , Svetlana Aminovna Madyarova , Sherali Eshonkulovich Janiev , Gaybulla Saypillaevich Khamidov (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This article is written with the aim of scientifically substantiating the theoretical foundations of the formation of the creative competence of future teachers in the process of teaching. The following tasks are defined in the article: a review of literature and concepts, development of a model for the formation of creative competence of future teachers in the process of teaching.